2012
DOI: 10.1073/pnas.1203823109
|View full text |Cite
|
Sign up to set email alerts
|

piggyBac transposition into primordial germ cells is an efficient tool for transgenesis in chickens

Abstract: Transgenic birds embody one of the most potent and exciting research tools in biotechnology for agriculture, medicine, and model animals. To date, retrovirus-or lentivirus-mediated transgenesis has been established in chickens and quail. However, despite having a valid technique for viral transduction to achieve transgenic birds, many obstacles exist for practical applications because of relatively low and variable rates of germ-line transmission and transgenic offspring showing transgene silencing, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
153
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(160 citation statements)
references
References 22 publications
4
153
2
1
Order By: Relevance
“…At this time, chicken PGCs can be successfully maintained in vitro without the loss of germ cell integrity (32,33), and generating transgenic chickens is feasible using transposon elements in cultured chicken PGCs (18,34). This study demonstrated the creation of specific knockout chickens using TALENs.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…At this time, chicken PGCs can be successfully maintained in vitro without the loss of germ cell integrity (32,33), and generating transgenic chickens is feasible using transposon elements in cultured chicken PGCs (18,34). This study demonstrated the creation of specific knockout chickens using TALENs.…”
Section: Discussionmentioning
confidence: 96%
“…In a previous report (18), we established a male chicken PGC line (SNUhp26) from WL embryonic gonads at day 6 (stage 28). The SNUhp26 PGC line was maintained and subpassaged with knockout DMEM (Invitrogen) supplemented with 20% FBS (Invitrogen), 2% chicken serum (Sigma-Aldrich, St. Louis, MO), 1× nucleosides (Millipore, Temecula, CA), 2 mM L-glutamine, 1× nonessential amino acids, β-mercaptoethanol, 10 mM sodium pyruvate, 1× antibiotic-antimycotic (Invitrogen), and human basic fibroblast growth factor (10 ng/mL; Koma Biotech, Seoul, Korea).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chicken as an acceptance model organism (Cogburn et al 2007) have advantages of population distribution and samples can be obtained easily. PGCs have been obtained mainly from germinal crescent (Petitte et al 1990, Park andHan 2012) and embryonic blood (van de Lavoir et al 2006, Macdonald et al 2010, Miyahara et al 2014, Naito et al 2015. However, their numbers have been quite limited (Park et al 2003) and couldn't provide sufficient materials for the transgenic manipulation (Shiue et al 2009).…”
Section: Introductionmentioning
confidence: 99%